2018
DOI: 10.1002/clc.22939
|View full text |Cite
|
Sign up to set email alerts
|

A clinical and proteomics approach to predict the presence of obstructive peripheral arterial disease: From the Catheter Sampled Blood Archive in Cardiovascular Diseases (CASABLANCA) Study

Abstract: A clinical/biomarker score demonstrates high accuracy for predicting the presence of PAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
(40 reference statements)
0
11
0
Order By: Relevance
“…As such, ML models might contribute to identify asymptomatic PAD patients with great functional limitations, that otherwise would be lost to PAD diagnosis by regular tests [ 142 ]. Other authors described that the combination of proteomic data and clinical information rendered algorithms able to predict angiographically significant PAD [ 143 ]. Regarding CV risk stratification, Ross EG et al reported that state of the art ML algorithms outperformed stepwise logistic regression models for the identification of PAD and the prognostication of mortality risk in this population [ 144 ].…”
Section: Machine Learning and Padmentioning
confidence: 99%
“…As such, ML models might contribute to identify asymptomatic PAD patients with great functional limitations, that otherwise would be lost to PAD diagnosis by regular tests [ 142 ]. Other authors described that the combination of proteomic data and clinical information rendered algorithms able to predict angiographically significant PAD [ 143 ]. Regarding CV risk stratification, Ross EG et al reported that state of the art ML algorithms outperformed stepwise logistic regression models for the identification of PAD and the prognostication of mortality risk in this population [ 144 ].…”
Section: Machine Learning and Padmentioning
confidence: 99%
“…Though prevalent in patients with DM, PAD is a challenge to identify and manage; tools typically used for diagnosis of PAD are often less accurate in those with DM. Accordingly, we wished to verify the performance of a biomarker-leveraged scoring system derived using machine learning recently found to predict angiographically significant PAD 8. We demonstrate excellent performance of the model in patients with DM.…”
Section: Discussionmentioning
confidence: 94%
“…The derivation of the HART PAD panel has been previously described 8. Briefly, using the same 354 patients included in this study, we used machine learning, a subset of artificial intelligence, to identify predictors of significant PAD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Machine learning (ML) encompasses a wide variety of methods whereby artificial intelligence learns to perform tasks when exposed to large amounts of data. The application of a ML algorithm may expedite management and identification of ACS for more accurate diagnosis, appropriate signposting to the correct clinical pathway and early initiation of appropriate ACS pharmacotherapy [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%